2014
DOI: 10.12944/cwe.9.3.18
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Magnetic Water Technology in Farming and Agriculture Development: A Review of Recent Advances

Abstract: Magnetic water treatment (MWT) techniques have shown promising potentials in different areas specially agriculture. Safety, compatibility and simplicity, environmentally friendliness, low operating cost and not proven harmful effects are the main advantages of electromagnetic field (EMF) over conventional methods for water treatment. Magnetized or magnetic water (MW) possesses unique physical and chemical characteristics making it a multi-purpose compound with potential benefits in medical treatment, industria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 38 publications
(85 reference statements)
3
32
0
3
Order By: Relevance
“…Data illustrated in Fig. 8 show that values of chemically available K concentration in the studied soil columns followed a trend almost similar to those attained previously with N and P. These results agree with those obtained by Shalaby (2012) and Ali et al (2014).…”
Section: Sodium Adsorption Ratio (Sar)supporting
confidence: 90%
See 1 more Smart Citation
“…Data illustrated in Fig. 8 show that values of chemically available K concentration in the studied soil columns followed a trend almost similar to those attained previously with N and P. These results agree with those obtained by Shalaby (2012) and Ali et al (2014).…”
Section: Sodium Adsorption Ratio (Sar)supporting
confidence: 90%
“…Studies have demonstrated that using MW for irrigation can improve water productivity; thus, conserving water supplies for the expected future global water scarcity. In addition, MW is reportedly effective at preventing and removing scale deposits in pipes and water containing structures (Ali et al, 2014). The main functions of magnetic treated water in soil are increasing the leaching of excess soluble salts, lowering pH values of soil layers, dissolving slightly soluble salts such as carbonates, phosphates and sulfates (Hilal et al, 2013), decreasing the hydration of salt ions, accelerating coagulation and salt crystallization, increasing the efficiency of added fertilizers, increasing nutrient mobility in soil and enhancing extraction and uptake of N, P, K, Fe and Zn by plants (Shalaby, 2012 andAli et al, 2014), improving the microbiological content of soil (Ratushnyak et al, 2008) and making plants more resistant to unfavorable environmental conditions (Alikamanoglu and Sen, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an increase in nutrient uptake was reported as a result of using magnetic treatment [38,39]. Furthermore, it was recorded that magnetically treated water increases nutrient mobility in soil and enhances extraction and uptake of P, K, N and Fe by plants [39,40]. The stimulatory impact of magnetic treatment was also attributed to the increase of the availability of minerals in soil through boosting the solubility of salts and minerals [41].…”
Section: Discussionmentioning
confidence: 99%
“…The MTIW has a high solubility [42,43]; therefore, nutrients are more soluble in water [39]. In fact, magnetic treatment of water restructures the water molecules into very small clusters, each made up of six symmetrically organized molecules [40]. The size of molecule groups gets reduced below the diameter of capillaries in the roots of plants thus it can easily enter the passageways in plant cell membranes [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation